THE CORRELATION BETWEEN THE ROLE OF NURSES AS EDUCATORS AND MEDICATION ADHERENCE IN DIABETES MELLITUS PATIENTS AT RAWALUMBU BEKASI HOSPITAL IN 2023 - Sitopu, Lusiana Hotmaria; Simamora, Rotua Suriany; Ani Anggraini (Rena Cipta Mandiri, 2024)
Diabetes Mellitus (DM) known in Indonesia as